Berit Olam - studies in Hebrew narrative & poetry : Genesis - Cotter, David W (Collegeville, Minnesota. The Liturgical Press., 2003)
The central thesis underlying this study of Genesis is that the God who is revealed as a character in Genesis is always a savior. In Genesis, David Cotter, helps readers discern a structure in the book whereby the least and the weakest are the object of God's saving help. Cotter begins with an introduction to the methodology that is used throughout the book. The introductory essay deals with the theory of Hebrew narrative and the challenges posed to biblical exegesis by contemporary literary theory. The theme of the commentary itself is that the God who is revealed as a character in Genesis is always a savior
"A Michael Glazier book"
Includes bibliographical references (pages 339-349) and indexes
Keywords: Bible. -- Criticism, interpretation, etc